2000
DOI: 10.1093/ije/29.2.214
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the interaction between familial and reproductive factors on the risk of breast cancer according to age, menopausal status, and degree of familiality

Abstract: A possible influence of reproductive and menstrual factors on familial risk of BC has been suggested previously and was also evident in the present study. Three-way interactions between age, family history and parity or age at first childbirth might exist and they merit further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 36 publications
3
18
0
Order By: Relevance
“…However, these results were attenuated when adjusted for age at first full-term pregnancy, indicating that age at first fullterm pregnancy was a stronger predictor than number of full-term pregnancies in determining BC risk in this population. The positive associations that we observed between BC and the interval between age at menarche and first full-term pregnancy are consistent with previous results [12,13].…”
Section: Discussionsupporting
confidence: 93%
“…However, these results were attenuated when adjusted for age at first full-term pregnancy, indicating that age at first fullterm pregnancy was a stronger predictor than number of full-term pregnancies in determining BC risk in this population. The positive associations that we observed between BC and the interval between age at menarche and first full-term pregnancy are consistent with previous results [12,13].…”
Section: Discussionsupporting
confidence: 93%
“…However, we observed that only 19% were found not to be at extra risk when four important factors were considered (21,22). The proportion of those who knew they were at some risk is similar what was found among Australian women, at 5% (23).…”
Section: Discussionsupporting
confidence: 80%
“…Evidence suggests that there is an interaction between marital status and parity [7], supporting a 'dual effect' of parity on breast cancer risk with pregnancy. Studies have shown that interactions between age, family history of breast cancer and parity might exist [8]. In addition, studies have reported that nulliparity reduces risk for breast cancer at younger age and elevates risk in the elderly [9,10].…”
Section: Discussionmentioning
confidence: 99%